LITERATURE REVIEW : EFFECTIVENESS OF BINAHONG (Anredera cordifolia (Ten.) Steenis) DECOCTION OF WATER FOR POST-PARTUM HEALING OF PERINEAL WOUNDS - Evi Nur Maulid Diana (Universitas Pahlawan, 2022)
Abstract As many as 75% of mothers who gave birth vaginally or vaginally experienced tissue tears or injuries to the perineum, where there is a potential prognosis or diagnosis in postpartum women with perineal sutures, namely infection of the perineal sutures. To prevent this infection, comprehensive perineal wound care is needed. Treatment of perineal wounds using binahong leaves can be one way to prevent infection in the wound. There are several studies that have proven that binahong leaves are effective in accelerating the healing process of perineal wounds in postpartum women. Research Objectives: This literature review aims to determine the effectiveness of binahong leaves in the healing process of perineal wounds in postpartum women. Methods: reviewing research articles both nationally and internationally obtained from Google Scholar using the keywords